Elevating Customer Satisfaction: The Crucial Role of Electronic Service Quality in Today’s Digital Landscape - Abusalma, Abdallah; Al-Daoud, Khaleel Ibrahim; Mohammad, Suleiman Ibrahim; Vasudevan, Asokan (International Review of Management and Marketing, 2024)
With digital platforms having proved to be a hub for service delivery, the drivers of customer satisfaction have become very important in ensuring improvement in service quality and retaining customers. This paper investigates the dimensions of electronic service quality that influence customer satisfaction in Jordan’s logistics and delivery service. The approach is quantitative, and data was collected through structured questionnaires from 436 logistics and delivery service users. The key measurement dimensions in the study will be reliability, ease of use, efficiency, privacy, and responsiveness. Research results show that reliability is the main influencer in affecting customer satisfaction; responsiveness and ease of use are closely followed. Efficiency and privacy too show positive influences, though relatively low. That will mean that logistics and delivery service industries that offer reliable and responsive services will result in customer satisfaction. These e-service factors indicate greater room for improvement, which service providers are encouraged to focus on to nurture better customer loyalty. The following sections provide valuable insights for industry leaders and policymakers who aim to enhance the overall customer experience in Jordan’s blossoming digital service landscape.